Correction: Solution self-assembly of plasmonic Janus nanoparticles. Issue 3 (6th January 2021) - Castro, Nicolò; Constantin, Doru; Davidson, Patrick; Abécassis, Benjamin
Abstract : Correction for 'Solution self-assembly of plasmonic Janus nanoparticles' by Nicolò Castro et al., Soft Matter, 2016, 12, 9666–9673, DOI: ; 10.1039/C6SM01632D .